2013
DOI: 10.1016/j.bbr.2012.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic low- and high-dose nicotine on cognitive flexibility in C57BL/6J mice

Abstract: The addictive nature of nicotine remains a global health problem. Despite the availability of treatments for smoking cessation, relapse to smoking after quit attempts still remains very high. Here, we evaluated the effects of chronic nicotine in male C57BL/6J mice in an operant cognitive flexibility task that required the animals to progress sequentially through multiple phases including visual discrimination, strategy shifting and response reversal. As frontostriatal circuits involving discrete regions of dor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 88 publications
5
49
2
Order By: Relevance
“…The same study also reported that intradimensional set-shifting that entails switching within the same dimension was also facilitated by acute nicotine. However in a recent study conducted in our laboratory, chronic nicotine treatment for 4 weeks did not alter strategy set-shifting in an operant-based cognitive flexibility task in mice (Ortega, Tracy, Gould, & Parikh, 2013). Rather, it impaired reversal learning and these cognitive deficits were associated with increased perseverative responding to the previously rewarded stimulus indicating deficits in response inhibition.…”
Section: Nicotine’s Effects On Adhdmentioning
confidence: 78%
“…The same study also reported that intradimensional set-shifting that entails switching within the same dimension was also facilitated by acute nicotine. However in a recent study conducted in our laboratory, chronic nicotine treatment for 4 weeks did not alter strategy set-shifting in an operant-based cognitive flexibility task in mice (Ortega, Tracy, Gould, & Parikh, 2013). Rather, it impaired reversal learning and these cognitive deficits were associated with increased perseverative responding to the previously rewarded stimulus indicating deficits in response inhibition.…”
Section: Nicotine’s Effects On Adhdmentioning
confidence: 78%
“…Mice were trained in an operant cognitive flexibility task using standard mouse chambers (Med Associates) as described previously in our studies (Ortega et al, 2013, Cole et al, 2015; D’Amore et al, 2015). Briefly, animals were autoshaped on a FR-1 schedule of reinforcement to acquire lever press responses and subsequent reinforcement of reward (10μl of 0.066% saccharin solution).…”
Section: Methodsmentioning
confidence: 99%
“…First,BDNF is known to play a critical role in nicotine-induced alterations incognitiveflexibility in mice [42]. Second, exogenous BDNF administration in mice facilitates set-shifting behavior by minimizing response perseveration [12], an effect that is dependent on activation of tropomyosin-related kinase B receptors on glutamatergic terminals.…”
Section: Discussionmentioning
confidence: 99%